The role of the cultural environment in the development of physical literacy and physical activity of Iranian children - Majid Mohammadi; Farzaneh Elahipanah; Sadegh Amani-shalamzari (BMC Pediatrics, 2023)
Abstract Background The investigation of physical literacy (PL) and physical activity (PA) should be done in an ecological context because the socio-cultural situation can encourage or inhibit children’s activity. The present study aimed to study the role of the cultural environment in the development of PL and PA in Iranian children. Methods The statistical population consisted of Iranian children aged 8 to 12, of whom 270 students were recruited by cluster sampling from six provinces. They complete the Canadian Assessment of Physical Literacy 2 (CAPL-2) and the International Physical Activity Survey. To examine the cultural environment, the components of geographic location (west, south, central, east, and northwest), place of residence (downtown, suburban, and village), and gender (boys and girls) were used. A multivariate ANOVA analysis was used to analyze the data. Results From the geographic location, the findings showed that students inhabit in the west and east of Iran have significantly higher scores than their counterparts living in the central, south, and northwest at PA and PL (P < 0.001). From the place of residence, we observed a higher level of PA and PL in children living in the village than in those living in the suburbs and downtown (P < 0.001). In terms of gender, boys have higher PL and PA scores (P < 0.001). Conclusion The findings demonstrate that socio-cultural factors, geographic location, place of residence, and gender have different impacts on children’s PL and physical activity. Therefore, we suggest using ecologically appropriate decentralized planning in a physical education curriculum.